VARIATION IN THE SENSITIVITY OF WANDERING JEW PLANTS TO GLUFOSINATE AMMONIUM - IVANA PAULA FERRAZ SANTOS DE BRITO; BRUNA BARBOZA MARCHESI; ILCA PUERTAS FREITAS E SILVA; CAIO ANTONIO CARBONARI; EDIVALDO DOMINGUES VELINI (Revista Caatinga, 2017)
This study aimed to identify the response of wandering jew (Commelina benghalensis L.) plants to different doses of glufosinate ammonium and the sensitivity of plants populations to the herbicide. Two studies were conducted, both in a greenhouse, and were repeated at different times. In the first study, two experiments were conducted to examine the dose-response curve using seven different doses of the glufosinate ammonium herbicide (0, 50, 100, 200, 400, 800, and 1600 g a.i. ha-1) with four replicates each. In the second study, which examined the range in sensitivity of wandering jew plants to glufosinate ammonium, 26 plants were sprayed with a dose of 200 g a.i. ha-1 herbicide. Visual assessments of percent injury and measurements of leaf tissue ammonium content were conducted. The use of untreated wandering jew control plants allowed for the correlation of glufosinate ammonium treatment with the ammonium concentrations in treated plant tissues; the ammonium concentration increased as a function of herbicide application, albeit not linearly with the dose. Ammonium content varied among individuals of the wandering jew plant population.